Best practices in engaging online learners through active and experiential learning strategies - Budhai, Stephanie Smith; Skipwith, Ke'Anna Brown (New York, NY Routledge, 2017)
Best Practices in Engaging Online Learners Through Active and Experiential Learning Strategies is a practical guide for all instructors and instructional designers working in online or blended learning environments who want to provide a supportive, engaging, and interactive learner experience. This book explores the integration of active and experiential learning approaches and activities including gamification, social media integration, and project- and scenario-based learning, as they relate to the development of authentic skill-building, communication, problem-solving, and critical-thinking skills in learners. Readers will find guidelines for the development of participatory peer-learning, cooperative education, and service learning opportunities in the online classroom. In addition, the authors provide effective learning strategies, resources, and tools that align learner engagement with course outcomes.
Engagement beyond the discussion board -- Experiential learning (cooperative education, internships, practicums, service-learning, and study abroad) -- Project and scenario-based learning -- Gamification and social media -- Building social presence through participatory and peer-learning opportunities -- Assessment of active and experiential learning.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Experiential learning; Education -- Organizations & Institutions; Active learning; Internet in education; Web-based instruction